2022
DOI: 10.3390/app12146899
|View full text |Cite
|
Sign up to set email alerts
|

Effect of Scents on Gazing Behavior and Choice

Abstract: Environmental stimuli can have a significant impact on our decisions. Elements of the store atmosphere, such as music, lights and smells, all have effects on choices, but these have been only vaguely investigated. In the present study, we aim to uncover the effect of strawberry scent on the gazing behavior and choices of the 62 recruited participants. A static eye-tracker was used to study the effect of scent, released by a diffuser. In total, 31 participants completed the study under odorless conditions, whil… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 6 publications
(1 citation statement)
references
References 55 publications
0
1
0
Order By: Relevance
“…The results demonstrated that time to first fixation and first fixation duration parameters are influenced by the presence of strawberry odor. Previous studies reported that first fixation duration might be influenced by odors (Seo & Hummel, 2009), however, recent studies demonstrated that this effect is dependent on the product being evaluatued (Szakál et al, 2022). Odors have been identified as being able to 'grab' participants visual attention and to drive it to conguent images, however, the role of odors in final decisions is considered minor as there are multiple other factors influencing the final decision (Yang et al, 2023).…”
Section: Discussionmentioning
confidence: 99%
“…The results demonstrated that time to first fixation and first fixation duration parameters are influenced by the presence of strawberry odor. Previous studies reported that first fixation duration might be influenced by odors (Seo & Hummel, 2009), however, recent studies demonstrated that this effect is dependent on the product being evaluatued (Szakál et al, 2022). Odors have been identified as being able to 'grab' participants visual attention and to drive it to conguent images, however, the role of odors in final decisions is considered minor as there are multiple other factors influencing the final decision (Yang et al, 2023).…”
Section: Discussionmentioning
confidence: 99%